2019
DOI: 10.1159/000495077
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ultrasonic Communication to Maintain Social Cohesion in the Javan Slow Loris (Nycticebus javanicus)

Abstract: Only a handful of primate taxa use ultrasonic vocalisations (those ≥20 kHz) to communicate. The extent and uses of ultrasonic communication remain poorly understood, potentially ranging from echolocation, advertisement of reproductive status and resource availability, social cohesion, to predator avoidance. Here, using active acoustics whereby the study subjects were observed throughout their activity period, we describe the first purely ultrasonic call from a strepsirrhine primate (family Lorisidae), recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Studies have reported that vocalizations often accompany social behaviors (Daschbach et al, 1981; Zimmermann, 1985). A recent study in Javan slow loris reported that the lorises used ultrasonic vocalizations for communication (Geerah et al, 2019), and reported that lorises emitted vocalizations in the context of following or leading each other, and entering a sleep site. In this study, we sometimes observed that the pygmy slow lorises looked into a nest box where another individual was already inside, or kept in social proximity for a while in front of the nest box before entering the box together.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that vocalizations often accompany social behaviors (Daschbach et al, 1981; Zimmermann, 1985). A recent study in Javan slow loris reported that the lorises used ultrasonic vocalizations for communication (Geerah et al, 2019), and reported that lorises emitted vocalizations in the context of following or leading each other, and entering a sleep site. In this study, we sometimes observed that the pygmy slow lorises looked into a nest box where another individual was already inside, or kept in social proximity for a while in front of the nest box before entering the box together.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that vocalisations often accompany social behaviors (Daschbach, Schein, & Haines, 1981; Zimmermann, 1985). A recent study in Javan slow loris reported that the lorises used ultrasonic vocalisations for communication (Geerah, O’Hagan, Wirdateti, & Nekaris, 2019), and reported that lorises emitted vocalisations in the context of following or leading each other, and entering a sleep site. In this study, we sometimes observed that the pygmy slow lorises looked into a nest box where another individual was already inside, or kept in social proximity for a while in front of the nest box before entering the box together.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, such potential predators still could perceive contrast. Slow lorises are highly cryptic, communicating in the ultrasonic range and moving slowly without leaping or disrupting vegetation [ 32 ]. If this cryptic strategy should fail and the loris is spotted by a predator, possession of a powerful aposematic signal could be an advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Javan slow lorises largely live in uni-male, uni-female social groups with 1–3 offspring in heavily defended territories [ 21 ]. From our long-term field work, we know that pairs can maintain these territories for up to eight years, meaning that the establishment of a permanent territory is a vital component of slow loris development [ 32 ]. Distinct facial features may communicate a warning signal, indicating aggressiveness of young animals looking to settle in a permanent home range, such as also seen in sciurids [ 2 ] and blue-ringed octopus (Hapalochlaena lunulata) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%